Improvisation with laptops. - Stout, David (Contemporary Music Review, 2006)
The author offers his thoughts on musical improvisation with laptop computers. As a laptop performer, the author considers his work as a painter, dancer, composer and video-maker. He describes how he achieved the goal for complexity, nuance and precision in digital video-music compositions. He also discusses the benefits of using interactive media in live musical performances.